Pengaruh Kemandirian Belajar, Cara Belajar, Dukungan Orang Tua Dan Teman Sebaya Terhadap Hasil Belajar Ekonomi Kelas XI IPS SMA Negeri 9 Sijunjung Melalui Variabel Motivasi - Nurul Saqinah; Citra Ramayani; Yosi Eka Putri (STKIP PGRI Sumatera Barat, 2023)
This study aims to analyze: 1) the effect of independent learning on learning motivation. 2) the influence of learning methods on learning motivation 3) the effect of parental support on learning motivation. 4) the influence of peers on learning motivation. 5) the influence of independent learning on learning outcomes. 6) the influence of learning methods on learning outcomes. 7) the effect of parental support on learning outcomes. 8) peer influence on learning outcomes. 9) the effect of learning motivation on learning outcomes. The type of research used in this research is descriptive associative research. The population of this study were students of class XI IPS SMA N 9 Sijunjung in the 2021/2022 academic year, totaling 104 students. Sampling technique with total sampling with a total sample of 104 students. The data analysis technique used is descriptive analysis technique and inductive analysis, using Path Analysis with the help of SPSS version 16.0 and Eviews 8 programs. The results showed that: First, learning independence had a significant effect on learning motivation, the path coefficient value for learning independence was 0.332. This coefficient value is significant because the tcount value is 4.313 > and tTable is 0.05 (1.66055). The two ways of learning have a significant effect on learning motivation, the coefficient value of the learning path is 0.235. This coefficient value is significant because the tcount value is 3.088 > and tTable is 0.05 (1.66055). The three parental support have a significant effect on learning motivation, the path coefficient value of parental support is 0.250. This coefficient value is significant because the tcount value is 3.292 > and tTable is 0.05 (1.66055). The four peers have a significant effect on learning motivation, the peer coefficient value is 0.198. This coefficient value is significant because the tcount value is 2.595> and tTable is 0.05 (1.66055). The five learning independence have a significant effect on learning outcomes, the coefficient value of the path of learning independence is obtained of 0.248. This coefficient value is significant because the tcount value is 4.313 > and tTable is 0.05 (1.66055). The direct effect of learning independence on learning outcomes is 6.1%. While the indirect effect of learning independence on learning outcomes through learning motivation is 2.2%. The total effect of learning independence on learning outcomes is 8.3%. The six ways of learning have a significant effect on learning outcomes, the coefficient value of the learning path is 0.170. This coefficient value is significant because the tcount value is 2.525 > and tTable is 0.05 (1.66055). The direct effect of learning methods on learning outcomes is 2.9%. While the indirect effect of learning methods on learning outcomes through learning motivation is 1%. The seven parental support has a significant effect on teacher performance. The path coefficient value of parental support is 0.214. This coefficient value is significant because the tcount value is 3.162 > and tTable is 0.05 (1.66055). The direct effect of parental support on learning outcomes is 4.6%. While the indirect effect of parental support on learning outcomes through learning motivation is 1.4%. The total effect of parental support on learning outcomes is 6%. The eight peers have a significant effect on learning outcomes, the path coefficient value of the peer path is 0.184. This coefficient value is significant because the tcount value is 2.754 > and tTable is 0.05 (1.66055). The direct influence of peers on learning outcomes is 3.4%. While the indirect influence of peers on learning outcomes through learning motivation is 1%. The total influence of peers on learning outcomes is 4.4%. The nine learning motivations have a significant effect on learning outcomes, the path coefficient value for learning motivation is 0.265. This coefficient value is significant because the tcount value is 3.113 > and tTable is 0.05 (1.66055). To improve teacher performance, teachers must increase learning independence, learning methods, parental support, peers and learning motivation of economic class XI IPS students at SMA Negeri 9 Sijunjung. Keywords: Independent Learning, Learning Ways, Parental Support, Peers, Learning Motivation